THE IMPROVEMENT MECHANICAL BRAKE SYSTEM OF THE PASSENGER СAR (Transport systems and technologies, 2021)
A set of theoretical scientific researches is carried out in the work, which proves that with the use of different types of brake pads in passenger cars some elements of the typical design of the mechanical brake system need to be modernized.Analytical calculations of the brake lever transmission of passenger cars are performed on the basis of the 2D scheme-model. Due to this, ways to improve the most important elements of lever transmission in passenger cars under the conditions of composite pads are proposed.The analysis of the forces acting in the typical design of the lever transmission of a passenger car for different types of pads is performed. The strength of important elements of the mechanical brake system is calculated by applying the finite element method.It is proposed to use the capabilities of the software package Femap Siemens PLM Software, which allows you to optimize the elements of the mechanical system of passenger cars. An example of topological optimization of some elements of brake lever transmission of a passenger car is given.By improving the elements of the mechanical brake system for the use of composite pads in passenger cars, greatly simplifies their design, facilitates maintenance and repair, also reduces the weight of the system as a whole and cost and significantly increases the level of traffic safety.
Keywords: brake lever transmission, passenger car, brake pads, strength, optimization, improvement, syste.